2022
DOI: 10.21532/apfjournal.v7i1.210
|View full text |Cite
|
Sign up to set email alerts
|

Market Consequences and Real Earnings Management: Empirical Study in Indonesia

Abstract: This research examined the consequences of real earnings management. We analyzed real earnings management’s effects on two aspects of investment: capital market and earnings informativeness. We rely on the efficient market hypothesis theorized by Fama (1969)to predict the market and accounting consequences caused by real earnings management. Our population and samples are a non-financial company listed on the Indonesian Stock Exchange during 2013-2017. We conducted event studies that examine cumulative abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Several previous studies have reported on the key factors that cause corrupt practices through earning management, namely leverage, profitability, liquidity, and firm size (Syaputra, 2022), (Suhono, Muslih, & Pratama, 2021), (Prayitno, 2020) and (Yimenu & Surur, 2019). Earning management can cause financial difficulty (Sayidah et al, 2020) and negatively affect market return (Ramadan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have reported on the key factors that cause corrupt practices through earning management, namely leverage, profitability, liquidity, and firm size (Syaputra, 2022), (Suhono, Muslih, & Pratama, 2021), (Prayitno, 2020) and (Yimenu & Surur, 2019). Earning management can cause financial difficulty (Sayidah et al, 2020) and negatively affect market return (Ramadan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%